Reconstructing the Role of the Prosecutor's Office in Resolving Corruption Crimes in National Strategic Projects - Dedy Pranata; Amzulian Rifai; Nashriana Nashriana (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2026)
The Prosecutor's Office handling of corruption cases involving National Strategic Projects (PSN) has not been optimal, as evidenced by lenient sentences compared to the public prosecutor’s charges, recovery of state losses of less than 30%, and litigation processes lasting 3–5 years with significant costs associated with resolving corruption cases. However, Article 30C(d) of Law No. 11/2021 grants the Prosecutor's Office the authority to conduct penal mediation. This study aims to analyze the reconstruction of the Prosecutor's Office role through penal mediation during the investigation stage to ensure that the resolution of PSN corruption cases is faster, more efficient, and guarantees the recovery of state funds. This is a normative legal study employing a legislative and conceptual approach. The results of the study indicate three obstacles: structural, substantive, and cultural. The restructuring is carried out through a “Limited Penal Mediation” model for PSN corruption cases involving cooperative perpetrators, accompanied by administrative sanctions, verification by the Financial and Development Supervision Agency (BPKP), and oversight by the Deputy Prosecutor's Office for Supervision (Jamwas) and the Prosecutor General’s Commission (Komjak). It is recommended that the Prosecutor's Office issue a Regulation of the Prosecutor's Office (Perja) regarding Standard Operating Procedures (SOPs) for Penal Mediation in PSN Corruption Cases.